1989
DOI: 10.1017/s0022215100108436
|View full text |Cite
|
Sign up to set email alerts
|

Serum enzymes in head and neck cancer. IV: 5-nucleotidase

Abstract: Serum 5-nucleotidase levels have been estimated in a group of 50 patients with head and neck cancer. The mean value was significantly higher in patients compared to the controls. In patients with non-malignant growths, the activity was comparable with the controls. The increase was higher in patients with proliferative lesions than those with ulcerative growths. Enzyme activity was found to be increased with the advancement in the stage of cancer. The rise was comparatively higher in patients with cervical met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is very well established that CD39 and CD73 promote the tumor mass progression in different kinds of cancer [17] and that they act by modulating the immune system to ensure tumor progression [16]. Previous studies demonstrated a high CD73 activity in blood serum of patients with head and neck cancer [21] and with intracranial neoplasias [22]. Clayton and collaborators have shown that the supernatant of different kinds of tumor cells secreted exosomes with CD39 and CD73 activity, which modulated the isolated T-cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is very well established that CD39 and CD73 promote the tumor mass progression in different kinds of cancer [17] and that they act by modulating the immune system to ensure tumor progression [16]. Previous studies demonstrated a high CD73 activity in blood serum of patients with head and neck cancer [21] and with intracranial neoplasias [22]. Clayton and collaborators have shown that the supernatant of different kinds of tumor cells secreted exosomes with CD39 and CD73 activity, which modulated the isolated T-cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in head and neck cancer demonstrated that the serum expression of CD73 was increased in patients with cancer compared with healthy subjects and its enzymatic activity was associated with the stage of cancer. 26 Elevated blood levels of soluble CD73 were found in patients with colorectal cancer, prostate cancer and cervical cancer. [27][28][29] Recently published data from patients with colorectal cancer liver metastases show that high levels of soluble CD73 expression are associated with shorter survival.…”
Section: Discussionmentioning
confidence: 99%
“…Since a soluble form of human CD73 was identified (Thompson et al, 1987;Coade and Pearson, 1989), many studies were settled to understand the role of this form in inflammatory and tumor processes. In 1989, Lal and colleagues reported that CD73 expression in serum of head and neck cancer patients was higher than that in healthy subjects (Lal et al, 1989). Interestingly, the enzymatic activity increased with the advancement in the stage of cancer (Lal et al, 1989).…”
Section: Soluble Cd73 In Cancer Patientsmentioning
confidence: 99%
“…In 1989, Lal and colleagues reported that CD73 expression in serum of head and neck cancer patients was higher than that in healthy subjects (Lal et al, 1989). Interestingly, the enzymatic activity increased with the advancement in the stage of cancer (Lal et al, 1989). Of note, Lehto and Sharom in 1998 observed that the soluble form of CD73 is enzymatically more active than the membrane-bound variant (Lehto and Sharom, 1998).…”
Section: Soluble Cd73 In Cancer Patientsmentioning
confidence: 99%